Effects of blood flow restriction training on lower extremity maximum dynamic strength and isokinetic muscle strength among athletes: a systematic review and meta-analysis - Li, R.; Chee, C. S.; Kahar, J. A.; Kamalden, T. F. T.; Yang, K.; Gao, Z. (Journal of Human Kinetics, 2025)
This systematic review aimed to examine the effects of blood flow restriction training (BFRT) on lower extremity muscle strength of athletes. This study followed the PRISMA-P guidelines. A comprehensive search for literature up to August 2024 was conducted on Scopus, Web of Science, PubMed and EBSCOhost to determine the eligible studies based on the inclusion criteria. The Cochrane risk of bias assessment tool was employed to evaluate the methodological quality of studies, the certainty of the evidence was assessed utilizing the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE), and the subgroup analyses were conducted based on moderator factors. A total of sixteen studies with 366 healthy athletes aged 15-27 years were included in the meta-analyses. The results indicated a moderate to large effect size (ES) of BFRT on the isokinetic knee flexion peak torque (ES = 0.88; p < 0.05), lower extremity dynamic strength-1RM (ES = 0.99; p < 0.001), and isokinetic knee extension peak torque (ES = 1.47; p < 0.001). The findings of subgroup analysis revealed that BFR-RT training (ES = 1.20-1.95; p < 0.05), training frequency of = 3 times per week (ES = 1.13-1.16; p < 0.001), occlusion pressures of = 160 mmHg (ES = 1.32-2.23; p < 0.01) and cuff width of > 7 cm (ES = 1.84-11.84; p < 0.01) were more beneficial to isokinetic muscle strength. No significant difference was observed in training duration (p > 0.05). In conclusion, blood flow restriction training is effective in enhancing lower extremity muscle strength in healthy athletes.